Sistem Informasi Manajemen di Era IoT dan Cloud - Audya, Anggi; Pefrianti, Lenni; Saroni, Habi; Putri, Pujawati Kurnia; Indriani, Vivi; Srikandy, Yuyun Lili; Sitorus, Sahat Parulian (Universitas Labuhanbatu, 2026)
The rapid development of Internet of Things (IoT) and cloud computing technologies has significantly transformed the way organizations manage information. Management Information Systems (MIS) are no longer limited to data recording and reporting functions but have evolved into integrated systems capable of providing real-time information to support strategic decision-making. This article aims to examine the role, benefits, and challenges of implementing Management Information Systems in the era of IoT and cloud computing. The research method employed is a literature review, drawing on relevant journals, books, and scientific publications. The results indicate that the integration of IoT and cloud computing into MIS can enhance operational efficiency, data accuracy, and system flexibility. However, several challenges remain, particularly related to data security, privacy issues, and the readiness of human resources.